2011
DOI: 10.2215/cjn.01200211
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in Kidney Transplantation

Abstract: The metabolic syndrome is a constellation of clinical abnormalities related to insulin resistance and inflammation. The syndrome is now recognized as a risk factor for diabetes and cardiovascular disease in the general population. Recent studies suggest that the metabolic syndrome is common after kidney transplantation, also possibly being predictive of allograft loss and poor allograft function. The development or worsening of obesity plays a central role in the development of metabolic syndrome after kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 34 publications
(29 reference statements)
2
39
0
4
Order By: Relevance
“…Several adult studies have suggested that the presence of the metabolic syndrome is a potent predictor of patient and graft outcome [44,45] and that obesity is the primary pathology responsible for the development of the metabolic syndrome [4,[45][46][47][48], particularly as adipose tissue secretes adipokines, such as leptin, tumor necrosis factor alpha and interleukin-6 [49]. It is unsurprising, therefore, to see that the prevalence of the metabolic syndrome in children increases following transplantation, affecting between 20 and 40 % of individuals in the first 1-2 years post-transplantation, particularly with prolonged corticosteroid use [50,51].…”
Section: Cardiovascular Riskmentioning
confidence: 99%
“…Several adult studies have suggested that the presence of the metabolic syndrome is a potent predictor of patient and graft outcome [44,45] and that obesity is the primary pathology responsible for the development of the metabolic syndrome [4,[45][46][47][48], particularly as adipose tissue secretes adipokines, such as leptin, tumor necrosis factor alpha and interleukin-6 [49]. It is unsurprising, therefore, to see that the prevalence of the metabolic syndrome in children increases following transplantation, affecting between 20 and 40 % of individuals in the first 1-2 years post-transplantation, particularly with prolonged corticosteroid use [50,51].…”
Section: Cardiovascular Riskmentioning
confidence: 99%
“…First, as described in a review by Hricik, weight gain after kidney transplantation is common and occurs in a majority of recipients (2). There are several mechanisms that could explain this phenomenon, including the effect of immunosuppressive agents and the diet change due to the cessation of dialysis treatment (3).…”
Section: To the Editormentioning
confidence: 99%
“…1 , e, quando bem sucedido, proporciona melhor qualidade de vida em comparação com outros métodos dialíticos, contribuindo para o aumento da expectativa de vida e também beneficiando os pacientes nas esferas psicológica e emocional [2][3][4][5] . Esta modalidade de TRS apresenta números crescentes 6 .…”
Section: ____________________________________________________________unclassified